The antiquity of the Italian nation the cultural origins of a political myth in modern Italy, 1796-1943 - De Francesco, Antonino 1954- (Classical presences, 2014)
This book explores the political uses of Italy's antique past in the early nineteenth century, tracing how anti-romanism was transformed into a pillar of the nation-building process. It demonstrates the pivotal role played by this ancient heritage in the formation of modern Italian national identity